Can Zinc Oxide Nanoparticles Alleviate the Adverse Effects of Salinity Stress in Coffea arabica? - Jegnes Benjamín Meléndez-Mori; Yoiner K. Lapiz-Culqui; Eyner Huaman-Huaman; Marileydi Zuta-Puscan; Manuel Oliva-Cruz (Agronomy)
Salinity is one of the main limiting factors for agricultural production worldwide. Nanotechnology has emerged as a possible tool to improve plant tolerance to salt stress. However, the application of zinc oxide (ZnO) nanoparticles in agriculture raises questions about their safety and long-term impact. The objective of this study was to investigate the effects of foliar application of ZnO nanoparticles on the physiology and defense systems of coffee plants in the presence/absence of NaCl (150 mM). A foliar spray of ZnO-NPs (0, 50, and 100 mg L−1) was applied to coffee plants individually and in combination with simulated stress conditions. The results showed that the application of ZnO-NPs to plants under salt stress had both positive and negative effects. An increase in proline content ranging from 33% to 77% was detected in stressed plants treated with ZnO-NPs, in contrast to stressed plants that did not receive the application. CAT activity increased by 69.4% to 152.8% with the application of ZnO-NPs compared to plants under salt stress that did not receive the treatment. Additionally, the application of ZnO-NPs decreased H2O2 levels by up to 18.7% with respect to the control group. On the other hand, 45% higher Na+ accumulation was observed in NaCl-stressed seedlings treated with ZnO-NPs (50 mg L−1). MDA levels in stressed plants treated with ZnO-NPs increased by 3% to 50%. Furthermore, the combined effect of ZnO-NP (100 mg L−1) and salt resulted in a significant reduction in carotenoids, limiting their photoprotective function. The results obtained indicate the complex interaction between the application of ZnO-NPs and various physiological processes in coffee plants, including photosynthesis, antioxidant enzyme activity, and the generation of reactive oxygen species. This phenomenon requires detailed analysis to fully understand the response of coffee plants to ZnO-NPs’ application.